2007
DOI: 10.1002/ijc.23016
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate prostate cancer biomarkers in prostate needle biopsy specimens using proteomic analysis

Abstract: Although serum prostate specific antigen (PSA) is a well-established diagnostic tool for prostate cancer (PCa) detection, the definitive diagnosis of PCa is based on the information contained in prostate needle biopsy (PNBX) specimens. To define the proteomic features of PNBX specimens to identify candidate biomarkers for PCa, PNBX specimens from patients with PCa or benign prostatic hyperplasia (BPH) were subjected to comparative proteomic analysis. 2-DE revealed that 52 protein spots exhibited statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
102
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 46 publications
7
102
1
Order By: Relevance
“…Therefore, increased ECHS1 expression may lead to overproliferation of cancer cells. Consistent with previous reports regarding colorectal, prostate, and liver cancers [15,16,19,27,28], our results showed that ECHS1 is highly expressed in gastric cancer cells, correlated with the degree of cell differentiation. Attenuation of ECHS1 expression by shRNA inhibited BGC-823 cell proliferation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, increased ECHS1 expression may lead to overproliferation of cancer cells. Consistent with previous reports regarding colorectal, prostate, and liver cancers [15,16,19,27,28], our results showed that ECHS1 is highly expressed in gastric cancer cells, correlated with the degree of cell differentiation. Attenuation of ECHS1 expression by shRNA inhibited BGC-823 cell proliferation.…”
Section: Discussionsupporting
confidence: 93%
“…In recent years, ECHS1 has been implicated in many cancers, including breast, prostate, colon and liver cancer [14][15][16][17][18][19]. ECHS1 levels were found to be elevated in needle biopsy samples from prostate cancer patients [16] and in liver cancer cells [17,18]. Reducing ECHS1 expression in hepatocellular carcinoma cells with shRNA inhibits PKB activation and tumor growth in xenograft mice [19].…”
Section: Introductionmentioning
confidence: 99%
“…FKBP14 belongs to the FKBP family, which perform important biological functions in the cell. Several members of the FKBP family are established to contribute to carcinogenesis, including FKBP12 (5,6), FKBP65 (7) and FKBP52 (8)(9)(10), while other FKBPs are downregulated in human cancer, including FKBP38 (11). However, the functions of FKBP14 in human cancer remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…FKBP65 expression was increased in early benign lesions compared with normal mucosa (7). FKBP52 has been demonstrated to be overexpressed in breast (8), prostate (9) and hepatocellular carcinoma tissues (10). FKBP38 has also been found to be selectively downregulated in aggressive types of schwannoma tumor cell lines (11).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, SELDI-TOF-MS has been successfully applied in many types of tumors. A number of biomarkers in this process have been identified and further characterized, associated with cancers such as breast (16)(17)(18), liver (19)(20)(21), lung (22,23), prostate (24) and ovarian cancers (25). These studies suggest that SELDI-TOF-MS ProteinChip technology can distinguish cancer patients from normal subjects with relatively high sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%